TB ASMARA CADRES IN TB CASE DISCOVERY EFFORTS AT UPT PUSKESMAS KARAWACI BARU IN 2022 - Feriyeni, Dece; Dewi Purnamawati (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
Tuberculosis (TB) is an infectious disease and is one of the leading causes of death worldwide. One of the efforts to increase coverage of active TB findings is TB screening by TB cadres. This study aims to study TB case finding with the role of ASMARA TB cadres (TB Independent Screening Application). This research is qualitative. The informants are ASMARA TB cadres at UPT Puskesmas Karawaci Baru. Data was collected through a Focus Group Discussion (FGD). of 32 cadres. The results of the study obtained 4 themes, namely Theme 1: Correct understanding of cadres about the meaning, signs, symptoms, and transmission of TB, Theme 2: Cadre's knowledge of TB Contact Investigation, Theme 3: Barriers to TB Contact Investigation, Theme 4: Obstacles Individual, Environmental and Socio-Cultural. The results showed that the Asmara TB cadres had good knowledge about TB, but it was necessary to increase knowledge continuously. Cross-sectoral cooperation is still minimal, there is a lack of public knowledge about pulmonary TB, the distance to health facilities is quite far, local cultural values and education levels are low, the role of trained cadres is not optimal, and religious leaders and the community are less involved. Continuous health education efforts are needed with cadres and community leaders to increase awareness of early detection of TB.